Factors Affecting the investment capital attraction in Binh Duong province - TRAN, VAN DAT (Advances in Social Sciences Research Journal, 2021)
The study aims to explore the factors affecting the investment capital attraction in Binh Duong province, influencing the decision to choose Binh Duong as the investment place of investors. More than 90 samples from domestic and foreign investors surveyed in Binh Duong. The paper focuses on finding the impact of 9 factors of Infrastructure, Investment support policy, Investment environment, Investment industry advantages, Service quality, Local brand, Human resources, Competitive cost, Investment demand satisfaction "Human Resources" has been one of the variables which play a direct effect on the choice of investments in Binh Duong. Since then, the study offers valuable governance implications to improve the factors that are not yet good. At the same time promoting the strengths of the province.